Assessment of team skills during dragon boat training using VR devices - Liu Jia Le; Wei Wang (Scientific Reports)
Abstract This study aims to compare the effectiveness of learning teamwork skills (i.e., perspective-taking, synchrony, and communication) with VR devices against conventional dragon boat race training. Here, a total of 344 athletes from the National University of Physical Education and Sports of Ukraine were divided into two groups. Students in one group were using VR devices to practice, while students in the other group received traditional training. The data collection instruments comprised self-report assessment questionnaires. The present findings suggest that VR-based training is more effective in developing synchrony than conventional methods. Future research may consider other aquatics disciplines and expand the possibilities of sports training.